Development of Module Based on Higher Order Thinking Skills on Cylinder and Cone Matter - Indraswari, Nur Fitriyah; Raniati, Raniati; Aini, Kurratul (Jurnal Pendidikan Matematika (JUPITEK), 2025)
This study aims to develop a valid, practical, and effective Higher Order Thinking Skills-based learning module on Cylinders and Cones for SMP NU Sumenep seventh-grade students. This type of research is research and development with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected using tests and questionnaires. Material and media experts validated the results. The results of the study show: 1) the validity aspect obtained an average of 87.5% with the criteria of "very good", 2) The practicality aspect seen from student assessments after using the learning module, obtained an average of 84.5% with the criteria of "good", 3) The effectiveness aspect seen from the results of students' mathematical problem-solving abilities, obtained an average of 76% with the criteria of "good". Based on the study results, we can conclude that the learning module related to cylinders and cones is suitable for use in learning because it has met three criteria: valid, practical, and effective. The HOTS-based learning module, especially about cylinders and cones, is expected to increase students' curiosity about the material, which can indirectly also improve students' understanding